OPTIMALISASI PELAYANAN TERMINAL PENUMPANG TIPE C “STUDI KASUS : PERUBAHAN STATUS TERMINAL UBUNG DENPASAR DARI TIPE A MENJADI TIPE C“ - I Gusti Putu Anindya Putra; I Dewa Ketut Adi Pradnyana; I Kadek Wayu Widi Dhana (UNHI PRESS, 2022)
Ubung Terminal is one of the terminals located in North Denpasar District, Denpasar City. Ubung Terminal is a type C terminal which in 2016 underwent a status change from type A based on the Decree (SK) of the Mayor of Denpasar Number 188.45/1060/HK/2016. The objectives to be achieved are to determine the internal and external impacts of the change in the status of the Ubung Denpasar terminal and how to optimize the function of the Ubung Denpasar terminal. This study uses a qualitative method with SWOT analysis. The data in this study were taken through interviews, observation and documentation. The results of this study are a decrease in the number of passengers, a decrease in terminal income, incompatibility of terminal facilities, a decrease in the number of vehicles at the terminal, a decrease in the number of traders in the terminal, misuse of sidewalks, arbitrary parking, increasing passengers outside the terminal and a decrease in consumers of food stalls and hotels. near Ubung Denpasar terminal. The strategy for optimizing the function of the Denpasar Ubung terminal is to develop terminal infrastructure and apply the concept of transit oriented development (TOD).